A selection methodology on reasonable width of stabilized coal pillar for retracement channel in longwall working face - Shan, Pengfei; Meng, Zheng; Lai, Xingping; Xue, Xiongfei; Li, Chenwei; Wang, Jindong; Li, Wei; Zhang, Long; Xi, Bojia; Jiang, Hongjun (Frontiers in Earth Science, 2024)
In this paper, the No. 30201 working face of a specific colliery was determined as the study area in the Yushen mining area, China. The objective of this paper is to determine the optimal position for pressure regulation measures during the final mining stage. A mechanical calculation model for stabilized coal pillar was developed. The analytical solution for the front abutment pressure function was obtained. Limit equilibrium theory and beam theory were employed to compute the critical width value of the stabilized coal pillar. The analysis focused on examining the spatiotemporal relationship between the rotational deformation of the main roof and the stability of the retracement channel. The study utilized numerical simulation to investigate the failure characteristics of the surrounding rock and the stress redistribution in the stabilized coal pillar within the working face. Through comprehensive analysis, a reasonable width of 15 m for the stabilized coal pillar was determined and successfully implemented in field practices. A method of using Artificial Neural Network (ANN) to select the stabilized coal pillar width was proposed. The input characteristics of ANN were determined through theoretical analysis. Four models of BP, WOA-BP, PSO-BP, and CPSO-BP were trained. The calculation accuracy of each model is evaluated by three quantitative metrics: MAE, MRE, and RMSE. The MAE value of the CPSO-BP model is 0.9489, showing a reduction of 70.87% compared to the BP model, 55.84% compared to the WOA-BP model, and 51.26% compared to the PSO-BP model. The MRE value is 0.0559, which is 71.51%, 56.29%, and 53.24% lower than the other models, respectively. The RMSE value is 1.0617, which is 68.92%, 56.13%, and 53.03% lower than other models, respectively. The four models were employed to compute the width of the stabilized coal pillar. The values for the BP, WOA-BP, PSO-BP, and CPSO-BP models were 12.7 m, 16.3 m, 14.1 m, and 15.2 m, respectively, indicating that the CPSO-BP model can effectively determine the width of the stabilized coal pillar.